PENGARUH PERSIA DALAM SYAIR SUFI SYAIKH HAMZAH FANSURI - Syarifuddin Syarifuddin (Media Syari'ah, 2017)
Hamzah Fansuri, in addition to his role as a Sufi cleric archipelago in the XVI century, has contributed to the culture of Nusantara as well as putting large foundations were Malay poetic and aesthetic, which in turn influences the Indonesian and Malay literature until the twentieth century. His poetic ability is closely linked to the Arab and Persian influence that characterizes his authorship system, as will be critically analyzed in this article.